Glaucoma Screened at the Ophthalmology Clinic of PZaGa Hospital Androva Mahajanga, Madagascar. - Valisoa, Rasoanirina Onja Tiana; Hariniaina, Andriambelo Ravaka; Gonzague, Miray Louis de; Tahiriniaina, Randrianarivelo; Mathieu, Andriamahenina Ando; Salle, Randrianirina Jean Baptiste de La; Léa., Raobela (Journal of Ophthalmology and Research, 2024)
Introduction: Glaucoma is an anterior optic neuropathy, usually bilateral but often asymmetric characterised by the association of pathological excavation of the optic disc, visual field alteration, an open or closed iridocorneal angle and often ocular hypertony. Materials and Methods: This was a prospective, cross-sectional, descriptive study over a period of 8 months from October 2017 to May 2018 carried out in the Ophthalmology Clinic of university hospital Professeur ZAFISAONA Gabriel Mahajanga. The purposes of this study were to determine the prevalence, identify the risk factors and describe the epidemio-clinical aspects of glaucoma. Results: Among the 3660 patients examined during the study period, 31 cases of glaucoma were diagnosed, representing a frequency of 0.84%. Male predominance was observed with a sex ratio of 2.10. The mean age was 65.07 +/- 0.12 years. Among the general risk factors for glaucoma recorded, hypertension ranked first with 38.70% of cases, followed by diabetes with 12.90% of cases. Local risk factors were previous eye surgery (10.82%), followed by eye trauma (6.45%). The visual field was agonic in 24.19% of cases and seven cases of total blindness were found (11.66%). Conclusion: Glaucoma was discovered late. All patients with a family history of glaucoma and aged 40 or over should be screened systematically during ophthalmological consultations.